FACTORS AFFECTING THE WORK STRESS OF POLICE OFFICERS: A SYSTEMATIC REVIEW - Rachma Yuniar Wijayanti; Hanandita Belva Fauzi (Psycho Idea, 2020)
Police officers are vulnerable to experience work stress, whatever the field or function they perform. The purpose of this literature study is to determine the factors that influence work stress on police officers. The journals used for review of this literature study were obtained from one  portal sources, namely Google Scholar. Search journals using keywords; "Work Stress," "Job Stress," "Police officers," "Work Stress Police Officers." "Obtained  five quantitative journals (N = 5) covering all criteria. Based on a review of the five journals, it is known that there are various factors that can influence the existence of work stress namely differences in the characteristics of each individual, the ability of individuals to deal with a problem, coping stress, role ambiguity, role conflict, role overload, exposure to critical incidents, discrimination at work, lack of cooperation among co-workers, and job dissatisfaction, organizational justice (at work, lack of quality sleep, lack of motivation or support from outside, past trauma and low psychological power or stress control that affect the coping used.